2012
DOI: 10.4141/cjas2011-082
|View full text |Cite
|
Sign up to set email alerts
|

Bioperformance evaluation of various summer pasture and winter feeding strategies for cow-calf production

Abstract: Legesse, G., Small, J. A., Scott, S. L., Kebreab, E., Crow, G. H., Block, H. C., Robins, C. D., Khakbazan, M. and McCaughey, W. P. 2012. Bioperformance evaluation of various summer pasture and winter feeding strategies for cow-calf production. Can. J. Anim. Sci. 92: 89–102. Bioperformance of two summer pasture and four winter feeding cow-calf production strategies in the western Canadian Parkland was evaluated. Diet composition and animal data were collected over 5 production years. Each production year began … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In both reference years, corn was the preferred grain and silage crop for beef cattle in eastern Canada, while barley was the commonly fed grain and silage crop for beef cattle in western Canada (Hironaka and Freeze 1992;Sheppard et al 2015). The chemical composition of feedstuffs (Table S1, available as Supplementary material for this paper) was primarily based on Canadian sources (Abouguendia 1998;Stewart 1999;Lardner et al 2011;Legesse et al 2012;Lardner 2013; Saskatchewan Forage Council 2014), while nutrient requirements of various cattle categories within the beef production system were derived using NRC-based diet formulation software (NRC 1996; AARD 2011).…”
Section: Feeding Scenariosmentioning
confidence: 99%
“…In both reference years, corn was the preferred grain and silage crop for beef cattle in eastern Canada, while barley was the commonly fed grain and silage crop for beef cattle in western Canada (Hironaka and Freeze 1992;Sheppard et al 2015). The chemical composition of feedstuffs (Table S1, available as Supplementary material for this paper) was primarily based on Canadian sources (Abouguendia 1998;Stewart 1999;Lardner et al 2011;Legesse et al 2012;Lardner 2013; Saskatchewan Forage Council 2014), while nutrient requirements of various cattle categories within the beef production system were derived using NRC-based diet formulation software (NRC 1996; AARD 2011).…”
Section: Feeding Scenariosmentioning
confidence: 99%
“…The paddocks were renovated from 1980 to 1998 in side-by-side AG and G pairs (Legesse et al 2012). Glyphosate herbicide was initially applied on the regrowth prior to a killing frost, subsequently followed by two passes with a tandem disker in the fall.…”
Section: Experimental Pastures and Weather Measurementsmentioning
confidence: 99%
“…Legumes have higher protein content than grasses and, as a result, the protein requirements of growing animals can be met to a large degree by adequate legumes in the forage mix. Legesse et al (2012) found that alfalfaÁgrass pasture contained more crude protein, compared to grass pasture.…”
mentioning
confidence: 99%